Development of Monopoly Game Media Based on Local Wisdom of Mathematics Content on Quadrilaterals in Elementary Schools - Pradnyani, Ni Sri; Gusti Ngurah Sastra Agustika; I Wayan Sujana (Jurnal Pendidikan Multikultural Indonesia, 2024)
The lack of student motivation in the learning process greatly influences student learning outcomes, this is proven by the learning outcomes of 36 students obtaining an average of 33.36% as measured by the benchmark assessment criteria (PAP), 33.36% is included in the very high criteria. low. This research aims to develop a monopoly game development design based on local wisdom with mathematical content on rectangular material in elementary schools. The type and approach used in this research is a mixed approach. The development model used is the ADDIE model. The data collection methods used are observation, interviews, questionnaires, and tests. The data analysis techniques used are quantitative descriptive, qualitative descriptive, and inferential statistics. There were 36 test subjects in this research. The results of this development research were (1) research design using the ADDIE development model. (2) the feasibility of the monopoly game based on the content expert test of 95.45%, the instructional design expert test of 91.66%, the learning media expert test of 91.66%, the individual trial of 98.33%, the small group trial of 99.16%. (3) the results of the t-test calculations obtained tcount 16.5903 which was then compared with the ttable price at the 5% level with dk = (n1 – 1) obtained ttable 1.690, obtained tcount = 16.5903 > ttable = 1.690 so that H0 is rejected and H1 is accepted. It can be concluded that the Monopoly game based on local wisdom mathematical content on rectangular material is effectively applied to mathematical content in elementary schools.